Dual career competency questionnaire for athletes: psychometric properties of the Brazilian version - Grubertt, Guilherme Alves; Márquez, Sara; Serassuelo Junior, Helio (Frontiers in Psychology, 2023)
No studies have yet attempted to quantitatively measure the competencies of Brazilian student-athletes. Consequently, there are no validated measures suitable for this purpose. The aim of this research was to examine the psychometric properties and assess content validity, factorial validity, and evidence based on response processes of the Brazilian version of the Dual Career Competency Questionnaire for Athletes (DCCQ-A). The Brazilian DCCQ-A was administered to 745 student-athletes (Mage = 17.3 + 5.4; 54% female; 8% student-athletes with disabilities). Content validity coefficient analysis indicated clarity of language, theoretical pertinence, and practical relevance of the Brazilian DCCQ-A items. Confirmatory factorial analysis revealed excellent goodness-of-fit indices of the 4-factor structure model. Polytomous Rasch analysis demonstrated an acceptable adjustment of the items and good organization in the item response categories. Considering the psychometric strength of the Brazilian DCCQ-A, this instrument can contribute to the practical and research applicability of sport psychology, providing support to those involved with student-athletes' dual career by identifying their competencies and possible limitations.